CONCOMITANT DISEASES AND RISK FACTORS FOR THEIR DEVELOPMENT IN PATIENTS WITH HIV INFECTION OLDER THAN 40 YEARS - D. A. Gusev; S. A. Buzunova; A. A. Yakovlev; V. B. Musatov; L. V. Glyzhina; S. A. Bykov; E. A. Strebkova; F. I. Nagimova; T. N. Bulatova; O. N. Kononchuk; R. G. Yapparov; S. V. Zajcev; et al. (Журнал инфектологии, 2017)
Objective: Evaluation of CVD and their risk factors in Russian 40+ HIV-infected patients is a key objective of the study. Materials and Methods: A retrospective analysis of 1872 medical records of 40+ HIV-infected patients from 12 regions of Russia on HAART was performed, including assessment of CVD presence, their risk factors and 10-years CVD risk based on SCORE. All patients received ARV treatment; the average duration of admission was 5 years (1–2 years – 43%, 3–5 years – 29%, over 5 years – 28%). Results: High incidence of CVD was observed: hypertension – 48%, including cerebrovascular disease – 2%; CAD – 9%, including myocardial infarction – 6%. Analysis of cardiovascular risk factors showed that 19% were overweight, lipid metabolism disorders were detected in 30% of patients, diabetes in 5%. 51% of patients smoked, systematic intake of alcohol in 61% of patients. 69% of patients had a risk of fatal CVD within 10 years based on SCORE, 16% of patients had a high/very high risk. Analysis of metabolic parameters showed that 99,4% of patients needed lifestyle improvement measures, 85% needed lipid lowering medication. One third of patients were constantly taking cardiovascular medications. Conclusions: CVD and metabolic disorders are more common for 40+ HIV-infected patients than for general population. ART assessment in 40+ patients additionally to viral load and CD4 level, should include analysis of cardiovascular risk factors and comorbidities. In elder patients ART regimen choice is particularly important, considering the risks of development and/or progression of CVD and risk of drugdrug interactions development.